2007
DOI: 10.1111/j.1540-8175.2007.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Strain and Strain Rate Properties in Patients with Right Ventricular Myocardial Infarction

Abstract: This study demonstrates that right ventricular strain and strain rate were lower in patients with left ventricular inferior wall myocardial infarction with, compared to without, right ventricular infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Moreover, Antoni et al [23] demonstrated that a RV strain \22.1 % provided incremental value over clinical information, infarct characteristics and conventional RV function parameter to predict adverse outcome in post AMI patients. The absolute value of RV has been shown to be lower in patients with RVMI compared to those without RVMI [18,19]. RV dysfunction can be observed irrespective of the localization of MI.…”
Section: Screening Of Rv Dysfunction After Stemimentioning
confidence: 96%
“…Moreover, Antoni et al [23] demonstrated that a RV strain \22.1 % provided incremental value over clinical information, infarct characteristics and conventional RV function parameter to predict adverse outcome in post AMI patients. The absolute value of RV has been shown to be lower in patients with RVMI compared to those without RVMI [18,19]. RV dysfunction can be observed irrespective of the localization of MI.…”
Section: Screening Of Rv Dysfunction After Stemimentioning
confidence: 96%
“…Recently it was shown that strain and strain rate imaging is also useful for the evaluation of right ventricular (RV) function in pulmonary hypertension and RV diseases of different etiologies (RV infarction, arrhythmogenic RV dysplasia/cardiomyopathy) [48,[65][66][67][68][69][70].…”
Section: Clinical Applications and Future Directions Of Echocardiogramentioning
confidence: 99%
“…This percentage is unacceptably low compared to other non-invasive techniques like MRI or echocardiography which is considered as the gold standard for RV function assessment [6,[17][18][19].…”
Section: Discussionmentioning
confidence: 97%
“…The literature on the value of 12 leads exercise testing at late (4 weeks) RV function assessment in patients with inferior MI is scarce since investigators prefer to study echocardiography or MRI, the best methods for the diagnosis of RV dysfunction, undoubtedly more sensitive and more specific for these cases [6,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%